Safety and feasibility of video assisted thoracoscopic thymectomy for myasthenia gravis: a single centre experience - Gajbhiye, Raj N.; Bhanarkar, Hemant; Akulwar, Vikrant V.; Tirpude, Bhupesh; Jambhulkar, Niketan; Deshpande, Gayatri (International Surgery Journal, 2019)
Background: Myasthenia gravis (MG) is an autoimmune disease affecting acetylcholine postsynaptic receptor of voluntary muscles. Thymectomy is a mainstay in the treatment for myasthenia gravis with or without thymoma. For many years transsternal and transcervical thymectomy had been the most common approaches used, video assisted thoracoscopic thymectomy is still not accepted as approach of choice. We intend to study the role of Video assisted thoracoscopic thymectomy for myasthenia gravis in central Indian population. Methods: Study was conducted in single tertiary care institute from January 2015 to November 2018. It is a prospective study. Aims of the study were to evaluate the safety and feasibility of video assisted thoracoscopic thymectomy for patients of myasthenia gravis. All patients of myasthenia gravis who underwent underwent video assisted thoracoscopic thymectomy (VATS) were included in the study. Intraoperative and postoperative details were studied to assess the safety and feasibility of VATS for treatment of myasthenia gravis. Results: 16 patients including 7 men and 9 women with the mean age of 35.5 years were investigated. All patients had myasthenia gravis, 12 pts had thymoma while remaining 4 pts had normal thymus. Mean operating time was 104 mins, Mean intraoperative blood loss was 45 ml (range 20 to 60 ml). There was no major intraoperative or postoperative complication or mortality. Mean ICU stay and hospital stay was 33 hrs and 4.25 days respectively. Conclusions: VATS thymectomy is safe and effective approach for the treatment of MG with or without thymoma. MG treated by VATS resulted in comparable neurological outcomes to those associated with the transsternal approach.